Precision farming with smart ICT applications for natural resource conservation - BHAN, SURAJ; BHARTI, V. K.; BHARTI, SANDEEP; ., MEETALI; ., DEEPSHIKHA; BHARTI, SANJAY (Journal of Soil and Water Conservation, 2020)
A new global strategy to deal with every aspect of precision farming technology is utmost important. Precision farming is an approach to farm management that uses information technology (IT) to ensure that the crops and soil receive exactly what they need for optimum health and productivity. The new agricultural technology strategy, dubbed Fuse Technology, integrates telematics, data management systems and auto-guidance solutions that, together, have the potential to make farming much more productive and profitable by optimizing the use of resources and inputs The Farmers will need to turn to new technologies to meet the growing demand for food production in the world. The precision farming technologies help customers to become more efficient and save resources. Producing quality, nutritious and affordable food will be a huge challenge before the world. It is predicted that even with the limited resources and the smart ICT, a new hi-tech era will need to be ushered in where automation and data can help farmers address many challenges of the future. The Internet of Things (IOT) and Drone application in farming will bring revolution and vibrancy in future farming. Not only will they save on input costs, but also save the precious non-renewable resources as well as minimize the hazards of indiscriminate use of agrochemicals.